Trade Union Cooperation in Europe Patterns, Conditions, Issues - Furåker, Bengt (Springer Nature, 2020)
This open access book discusses transnational trade union cooperation in Europe - its forms, focuses, conditions, and obstacles. It provides an overview of existing trade union cooperation and includes detailed analyses of two specific questions: the debates on statutory minimum wages and the Posting of Workers Directive. Drawing on empirical research, the authors take a comparative approach, considering national industrial relations regimes as well as individual sectors. With the ongoing processes of integration in Europe, it has become increasingly important for unions to cooperate with regard to employers and EU institutions. The authors illustrate the interconnections between national and European industrial relations, and explore the process of European integration in labour markets. Illustrating the potential for and difficulties involved in deepening trade union cooperation across Europe, this work is a vital read for trade unionists, researchers and students interested in European trade unionism and labour markets.